A randomized controlled trial of SAFMEDS to improve chest radiograph interpretation among medical students. Issue 151 (June 2022) - Dunne, Kevin; Madden, Caoimhe; Byrne, Dara; McCarthy, Peter; O'Connor, Paul; Lydon, Sinéad
Abstract: Rationale and objectives: Junior doctors find chest radiograph (CXR) interpretation challenging, and commonly make diagnostic errors. The aim of this study was to evaluate the effectiveness of SAFMEDS in teaching undergraduate medical students to identify important chest abnormalities in radiology imaging. Materials and methods: A pragmatic randomized controlled trial design was utilized. Third-year medical students were randomly assigned to an intervention group ( n  = 20), who received the SAFMEDS intervention, or a control group ( n  = 20), who did not receive the intervention. Three participants (one intervention, two control) withdrew from participation. Percentage accuracy in CXR interpretation was assessed at three timepoints (baseline, post-test, and retention). A series of one-way between-subjects' analyses of covariance, with percentage accuracy at the pre-test timepoint entered as the covariate, were conducted. Results: Large effect sizes of the SAFMEDS intervention were observed at post-test and retention (η 2  = 0.67, η 2  = 0.58 respectively), with the intervention group demonstrating significantly higher percentage accuracy in CXR interpretation as compared to the control group at both timepoints. Intervention group performance decreased by 5.26% ( SD  = 9.80) from post-test to retention. Twelve intervention group participants (63.2%) met the fluency criteria. Despite large effect sizes, there were no significant differences in post-test or retention performance between fluent and non-fluent participants (η 2  = 0.17 and η 2  = 0.2 respectively). Conclusion: SAFMEDS offers an effective adjunct to usual teaching. Future research could focus on examining the effect of fluency with a larger sample, in addition the expansion of the SAFMEDS approach, and its' application to other health profession populations.